Management of degenerative cervical myelopathy – An update - JOAQUIM,ANDREI F. (2016)
SUMMARY Introduction Degenerative cervical myelopathy (DCM) is the most common cause of spinal cord dysfunction in adult patients. Patients generally present with a slow, progressive neurological decline or a stepwise deterioration pattern. In this paper, we discuss the most important factors involved in the management of DCM, including a discussion about the surgical approaches. Method The authors performed an extensive review of the peer-reviewed literature addressing the aforementioned objectives. Results Although the diagnosis is clinical, magnetic resonance imaging (MRI) is the study of choice to confirm stenosis and also to exclude the differential diagnosis. The severity the clinical symptoms of DCM are evaluated by different scales, but the modified Japanese Orthopedic Association (mJOA) and the Nürick scale are probably the most commonly used. Spontaneous clinical improvement is rare and surgery is the main treatment form in an attempt to prevent further neurological deterioration and, potentially, to provide some improvement in symptoms and function. Anterior, posterior or combined cervical approaches are used to decompress the spinal cord, with adjunctive fusion being commonly performed. The choice of one approach over the other depends on patient characteristics (such as number of involved levels, site of compression, cervical alignment, previous surgeries, bone quality, presence of instability, among others) as well as surgeon preference and experience. Conclusion Spine surgeons must understand the advantages and disadvantages of all surgical techniques to choose the best procedure for their patients. Further comparative studies are necessary to establish the superiority of one approach over the other when multiple options are available.